Relationship Between Corporate Social Responsibility (CSR) and Firm Value with Profitability as a Mediating Factor in Indonesian Mining Companies (2021–2023) - Prasasti, Yurike; Zulvia, Yolandafitri (Golden Ratio of Auditing Research, 2026)
Mining companies are key drivers of Indonesia’s economic growth. Their operations rely on the exploitation of non-renewable resources, which result in greater environmental and social impacts compared to other sectors. To maintain their reputation and sustain firm value, these companies must balance profit-oriented activities with Corporate Social Responsibility (CSR) initiatives as a form of environmental accountability. This study examines the direct effects of CSR disclosure and profitability on firm value, as well as the indirect effect of CSR disclosure on firm value through profitability as a mediating variable. The research focuses on mining companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. Using purposive sampling, 36 companies met the selection criteria. Data were analyzed using the Partial Least Squares (PLS) approach within a Structural Equation Modeling (SEM) framework, employing SmartPLS 4 software. The results reveal that CSR disclosure has a significant effect on firm value but no significant effect on profitability. In contrast, profitability has a significant positive effect on firm value. These findings suggest that CSR disclosure directly influences firm value rather than indirectly through profitability as a mediating variable.